RELIGION AND POLITICS: THE SIKH PERSPECTIVE - Bala, Shashi (Journal of Dharma, 2000)
Religion, in the real sense, is a spiritual force which stands for the unity and integrity of the cosmos. But a mere glance at the present scenario all over the world reveals the reality that the maximum violence and massacre of innocent human beings is taking place in the name of religion, caste and creed. The underlying factor seems to be the possession of religion rather than its practice. It is, therefore, imperative to delve deep into the cause of religious fanaticism and its challenges to the integrity of the nation.